Жабракi ў пахавальных i памiнальных абрадах беларусаў Падзвiння (па матэрыялах ХIХ – пачатку ХХI стагоддзя) - Аўсейчык, Уладзiмiр (Białorutenistyka Białostocka, 2021)
On the basis of folklore and ethnographic material of the 19th – early 21st century the symbolic status and ritual functions of beggars in funeral and memorial rites of Belarusian Dvina region are discussed. The beggars represent a peculiar social group, the specificity of which is most expressively manifested in the ritual forms of behavior, including the funeral and memorial rites of the dead. The reasons of their inclusion into the ritual sphere (through the analysis of such characteristics as poverty, physical deviations, blindness, special appearance, possession of secret knowledge, the nature of their “activity”, isolated lifestyle) are presented. The article deals with the status and ritual functions of beggars in the funeral rites and rites of the memorial cycle (within a year from the date of death and calendar holidays). New field material is involved in the study, part of which is fixed by the author. The results of the research will be useful in the study of worldviews and beliefs. Артыкул падрыхтаваны ў ходзе працы па праекце БРФФД-РФФД «Субкультура детства в дискурсе устной истории, языке и фольклоре Витебско-Псковского пограничья ХХ – начала ХХI века» (Г20Р-095 ад 4 мая 2020 г.). Auseichyk Uładzimir (Аўсейчык Уладзiмiр) — doktor nauk historycznych, Połocki Uniwersytet Państwowy, Katedra historii i turystyki (docent), Białoruś. Połacki Uniwersytet Państwowy, Białoruś Auseichyk U. Ya., Polauzrostavyia asablivastsi u tradytsyinai pakhaval’na-paminal’nai abradnastsi belarusau Padzvinnia, «Gender i problemy kommunikativnogo povedeniia», Novopolotsk 2010 [Аўсейчык У.Я., Полаўзроставыя асаблiвасцi ў традыцыйнай пахавальна-памiнальнай абраднасцi беларусаў Падзвiння, «Гендер и проблемы коммуникативного поведения», Ново- полоцк: ПГУ 2010]. Berk P., Narodnaia kul’tura Europy ranniaga Novaga chasu, Minsk 1999 [Бэрк П., Народная культура Эўропы ранняга Новага часу, Мiнск 1999]. Bogdanovich A.E., Perezhitki drevnego mirosozertsaniia u belorusov. Etnograficheskii ocherk, Grodno 1895 [Богданович А.Е., ...